Kipper's book of opposites - Inkpen, Mick. (London : Hodder childern, 1997)
Single-word descriptions of a playful dog's antics introduce pairs of opposites.
On board pages.
Keywords: Dogs -- Fiction; English language -- Synonyms and antonyms -- Fiction